DISTRIBUSI KOMPONEN KIMIA KAYU MAHANG (Macaranga hosei King) - Evy Wardenaar; Yeni Mariani; Harnani Husni; Farah Diba; Hikma Yanti (Universitas Tanjungpura, 2013)
This research aim was to know the chemical distribution of wood (Macaranga hosei King) based on its stem height/axial direction (base, middle and end of stem) and the depth of stem/radial direction (2/3 3/3 rays, 1/3 2/3 rays and 0 1/3 rays). The experimental includes the percentage of alcohol benzene-soluble extractive content, lignin content, holocellulose and ?- cellulose. The result showed base on stem height that the percentage of alcohol benzene soluble extractive, lignin, holocellulose and ?- cellulose content decrease from the base, middle and to the end of stem. Base on depth of stem, the result showed that the percentage of alkohol benzena-soluble extractive content, lignin content, holocellulose and ?- cellulose decreasing from 2/3 3/3 rays, 1/3 2/3 rays and to the part of 0 1/3 rays. The interaction of stem height and depth of stem has significantly affected to the percentage of alcohol benzene-soluble extractive content. The overall result showed that Mahang wood is suitable for used as sawn timbers, wood panels and raw materials for pulp and paper. Keywords: chemical properties, Macarang hosei, stem height, stem depth.